2017
DOI: 10.3390/molecules22061019
|View full text |Cite
|
Sign up to set email alerts
|

Leptadenia reticulata (Retz.) Wight & Arn. (Jivanti): Botanical, Agronomical, Phytochemical, Pharmacological, and Biotechnological Aspects

Abstract: Leptadenia reticulata (Retz.) Wight & Arn. (Apocynaceae), is a traditional medicinal plant species widely used to treat various ailments such as tuberculosis, hematopoiesis, emaciation, cough, dyspnea, fever, burning sensation, night blindness, cancer, and dysentery. In Ayurveda, it is known for its revitalizing, rejuvenating, and lactogenic properties. This plant is one of the major ingredients in many commercial herbal formulations, including Speman, Envirocare, Calshakti, Antisept, and Chyawanprash. The the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(34 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…Presence of flavonoids, phytosterols, terpenes and terpenoids, fatty acids, tannins, carbohydrates, glycosides, saponins, free catechols, starches and phenolic compounds was identified by various researchers in different solvent extracts of L. reticulata. 9 This plant has multiple therapeutic activities due to presence of various bioactive phytochemicals like stigmasterol, ß-sitosterol, α-amyrin, ß-amyrin, rutin, simiarenol, apigenin, reticulin, deniculatin, leptaculatin, l-α-tocopherol, p-coumaric acid, quercetin, phytol etc. 8 Present study gives a comparative account of various phytochemicals identified by GC-MS analysis in root, stem, leaves and callus.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of flavonoids, phytosterols, terpenes and terpenoids, fatty acids, tannins, carbohydrates, glycosides, saponins, free catechols, starches and phenolic compounds was identified by various researchers in different solvent extracts of L. reticulata. 9 This plant has multiple therapeutic activities due to presence of various bioactive phytochemicals like stigmasterol, ß-sitosterol, α-amyrin, ß-amyrin, rutin, simiarenol, apigenin, reticulin, deniculatin, leptaculatin, l-α-tocopherol, p-coumaric acid, quercetin, phytol etc. 8 Present study gives a comparative account of various phytochemicals identified by GC-MS analysis in root, stem, leaves and callus.…”
Section: Discussionmentioning
confidence: 99%
“…Liposomal nanoformulations for drug delivery have been significantly increasing in pharmacology. These formulations have benefitted from the stability, biodistribution on those drugs having bioavailability or high toxicity [172][173][174][175]. While treating liposome as alone in intravenous blood stream, it got cleared by immune system due to having short half-lives [172].…”
Section: Liposomes Nanoformulationmentioning
confidence: 99%
“…About 25% of the pharmaceutical compounds available today are derived from herbal resources (Mohanty, Swamy, Sinniah, & Anuradha, 2017). About 25% of the pharmaceutical compounds available today are derived from herbal resources (Mohanty, Swamy, Sinniah, & Anuradha, 2017).…”
Section: Herbal Antifungalsmentioning
confidence: 99%
“…A great section of modern medicines were originally derived from herbal sources. About 25% of the pharmaceutical compounds available today are derived from herbal resources (Mohanty, Swamy, Sinniah, & Anuradha, 2017).…”
Section: Herbal Antifungalsmentioning
confidence: 99%